MODEL OF ORGANIZATIONAL CULTURE IN HIGHER EDUCATIONAL INSTITUTION - Anna P. Istomina (Вестник Северо-Кавказского федерального университета, 2022)
The article focuses on certain elements of organizational culture in an institution of higher education as well as its structural and essential levels. There is a model proposed for organizational culture within a university based on the elements and levels in question.